Pengaruh Efek Hashtag Racuntiktok Terhadap Perilaku Konsumtif Mahasiswa Ilmu Komunikasi Universitas Islam Negeri Sumatera Utara - Rizky Amelia; Indira Fatra Deni; Fakhrur Rozi (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of the hashtag toxictok on the consumptive behavior of Communication Studies students at the State Islamic University of North Sumatra. In this study I used a descriptive quantitative method with a simple linear regression research technique. The population in this study were 300 respondents and the sample was 45 respondents. The theory used in this study is the dependent theory. The data collection instrument is a questionnaire. Data analysis used descriptive statistical analysis and simple linear regression analysis. The data processing was carried out with the help of SPSS Software Version 23. Based on the results of the hypothesis testing research, the results of the t test were tcount > ttable or or 8.074 > 2.016 with a significant level below 0.05, namely 0.000. Thus it is concluded that H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between the poison tiktok hashtag variables on consumptive behavior. Based on the results of the coefficient of determination (R2) it shows an R2 value of 0.700 = 70%. This shows that the percentage of the contribution of the poison tiktok hashtag to the consumptive behavior of UINSU Medan Communication Science students is 70%.